2008
DOI: 10.3801/iafss.fss.9-931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitiation on the heat release rate in mechanically-ventilated compartment fires

Abstract: The prediction of the heat release rate in compartment fires is still a challenging question due to the feedback of the environmental variables on the burning rate. A set of large-scale, mechanically-ventilated pool fire experiments supports the present analysis. Most of these tests yielded a quasi steady-state with limited pyrolysis compared to well-ventilated conditions. From a well-stirred reactor approach, the effect of vitiation on the steady-state pyrolysis rate is discussed. The Global Equivalence Ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…This is therefore to be considered as a limitation of the present model. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Finally, it is noted that the temperatures measured in [13] remained below 475 K [14]. Knowing that the vaporization temperature of HTP is 461 K, one can conclude that the thermal feedback effect in [13] is negligible, if not inexistent.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…This is therefore to be considered as a limitation of the present model. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Finally, it is noted that the temperatures measured in [13] remained below 475 K [14]. Knowing that the vaporization temperature of HTP is 461 K, one can conclude that the thermal feedback effect in [13] is negligible, if not inexistent.…”
Section: Resultsmentioning
confidence: 97%
“…It is noteworthy that Melis et al [14] examined additional experimental data (not shown here) where the air inlet was placed at a low position. They concluded that, in such configuration, the available oxygen near the flame base is significantly higher than the mean oxygen concentration, inducing therefore a behaviour more similar to naturally-ventilated fires.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations